2021
DOI: 10.2528/pierl21022104
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Thinning Useless Elements in the Planar Antenna Arrays

Abstract: In this paper, the thinning space is constrained to only outer sub-planar array elements instead of fully filled planar array. Since the amplitude weights of the outer elements have small amplitude excitations, they can be optimized to find the least useful elements and remove them without affecting the desired radiation characteristics. The binary genetic algorithm is used to perform such thinning optimization. Simulation results show that roughly the same performance can be achieved when the number of remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Also, it was reported that GA is not efficient in mitigating interfering sources as LMS [51,52]. On the other hand, the GA algorithm was proven to be an efficient for array thinning [27,30,31,36] so that it was utilized for thinning the proposed array design. In the LMS approach, the weights of antenna elements are calculated and updated recursively utilizing the steepest-descent method with a step size of 0.05 [53].…”
Section: B Ga-lms Beamforming Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was reported that GA is not efficient in mitigating interfering sources as LMS [51,52]. On the other hand, the GA algorithm was proven to be an efficient for array thinning [27,30,31,36] so that it was utilized for thinning the proposed array design. In the LMS approach, the weights of antenna elements are calculated and updated recursively utilizing the steepest-descent method with a step size of 0.05 [53].…”
Section: B Ga-lms Beamforming Resultsmentioning
confidence: 99%
“…Among which, the Particle Swarm Optimization (PSO) [28,29], Genetic Algorithm (GA) [27,30,31], Simulated Annealing (SA) [32,33], Ant Colony Optimization (ACO) [34], and Boolean Differential Evolution Algorithm (BDE) [35] were used. In [36], the binary GA technique was employed to optimize the excitations of the outer elements of planar antenna array and to reduce the number of active elements while preserving the desired radiation characteristics. In [37], a new stochastic optimization approach, called Slime Mold Algorithm (SMA), was investigated to design thinned concentric circular antenna arrays with lowest SLL and fixed HPBW.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regular fully populated transmitting arrays need a large number of array elements which could increase the cost of WPT systems [13]. To reduce the number of array elements, the synthesis of a sparse uniform amplitude concentric ring array (SUACRA) for MPT is discussed in [14,15]. Another new method based on subarray division is investigated in [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In all of those aforementioned methods, it is required to readjust (or redesign) the excitation weights of all or most of the active elements which are practically complex and time consuming. Moreover, they are only considered a very limited number of defective elements that are usually located randomly on the array sides and not on the array center [9,10]. As a matter of fact, the central array elements usually have the largest excitation weights which make their compensation difficult when they are facing faults.…”
Section: Introductionmentioning
confidence: 99%